MANAJEMEN PEMBELAJARAN PENDIDIKANKEWARGANEGARAAN DI SEKOLAH MENENGAH ATAS NEGERI 3 KAUR KABUPATEN KAUR - Tarmizi Tarmizi (Manajer Pendididikan, 2015)
The purpose of this research is to describe the management of citizentship education instructional in senior high school 3 Kaur. The methods of this research is qualitative descriptive.The result of this research conclude that the management of citizentship education instructional in senior high school 3 Kaur, the lack of students input quality, the lack of teachers quality andquantity, do not use variation of learning yet, the lack of students handbook, the quality and the quantity of the infrastructure is enough. Senior High school 3 Kaur needs performanced andstrategic manager to depelove creativity and use strong factor to handle the weakness.Keywords: learning, management, citizenship education